Effect of the Powerpoint Presentation on Academic Achievement of Agricultural Students Taught Digestive System of Animals in Nigeria - Emmanuel, Egunsola Abraham Olawuyi; Ferdinand, Felix; Ibanga, Isaac John (Journal of Pedagogy and Education Science, 2024)
This study investigated the effect of using PowerPoint presentations (PPP) as an instructional medium on the academic achievement of agricultural students in secondary schools in Adamawa State, Nigeria. The study employed a pre-test, post-test, non-equivalent control group quasi-experimental research design, with 88 students from secondary school as the sample. The participants were divided into an experimental group taught with PPP and a control group taught using conventional methods. An achievement test on the digestive system of animals was administered before and after the intervention. The data were analyzed using mean statistics and t-tests. The findings revealed that students with PPP achieved significantly higher academic scores than those taught using conventional methods. Furthermore, the male students outperformed their female counterparts in both groups. The results highlighted the effectiveness of PPP in capturing students' interest and enhancing academic performance in agricultural science. The study's outcomes align with previous research, emphasizing the benefits of using modern educational media for instructional purposes. In conclusion, the study recommends a shift from conventional teaching methods to educational media like PPP to enhance learning outcomes in agricultural science. Incorporating PPP into teaching can engage students' senses and promote a deeper understanding of the subject matter. The results also indicate that gender plays a role in academic achievement, suggesting the need for targeted interventions to support female students in their learning journey. Overall, the study underscores the potential of technology-based instructional approaches to improve students' academic achievements in secondary schools.